Fifty Shades of sex shop: Sexual fantasy for sale. (December 2013) - Martin, Amber
This article proposes that the extensive sales and widespread popularity of the Fifty Shades trilogy has placed BDSM in the sexual spotlight and explores how this is being capitalized upon by some sex shops and sex toy retailers by encouraging consumers to bring the erotic fiction of Fifty Shades into their own sexual reality through the purchase of particular commodities and the acquisition of BDSM related sexual knowledge. This article argues that this is based upon a particular ' Fifty Shades ' brand of BDSM that is constructed as fun, fashionable and exciting as opposed to extreme, marginalized and dangerous.